Comercio Internacional De Productos Agrícolas En El Departamento Del Meta Años 2016-2020 - Gil Montes, David Felipe (Universidad Antonio Nariño, 2022)
Globalization as an economic phenomenon of capitalism has become the main element of economic development for countries that must find a way to internationalize their economies by seeking markets outside their borders, thus taking advantage of the consumption needs of other economies that when buying the National products generate foreign currency to the countries that have a higher level of international transactions.